Analisis Penerapan Metode Just In Time Dalam Upaya Meningkatkan Efisiensi Biaya Produksi Pada PT. Bakrie Pipe Industries - Nafsi, Zakiatin; Widjanarko, Wirawan; Sumantyo, Franciscus Dwikotjo Sri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The business world is often one of the areas most affected by changing times. The increasingly competitive business environment requires companies to improve product quality while reducing production costs. This study aims to analyze the implementation of the Just In Time (JIT) method in efforts to improve production cost efficiency at PT. Bakrie Pipe Industries. The JIT method was chosen because it is believed to minimize waste, reduce storage costs, and accelerate production flow by ensuring the timely availability of raw materials and components. This study employs a quantitative approach by collecting production, cost, and operational efficiency data from the company for the 2024 period. The results indicate that the implementation of JIT at PT. Bakrie Pipe Industries positively contributes to reducing production costs, although increased production volume does not always result in optimal cost efficiency.